2023
DOI: 10.1038/s41375-023-01808-0
|View full text |Cite
|
Sign up to set email alerts
|

BET inhibitors rescue anti-PD1 resistance by enhancing TCF7 accessibility in leukemia-derived terminally exhausted CD8+ T cells

Abstract: Many acute myeloid leukemia (AML) patients exhibit hallmarks of immune exhaustion, such as increased myeloid-derived suppressor cells, suppressive regulatory T cells and dysfunctional T cells. Similarly, we have identified the same immune-related features, including exhausted CD8+ T cells (TEx) in a mouse model of AML. Here we show that inhibitors that target bromodomain and extra-terminal domain (BET) proteins affect tumor-intrinsic factors but also rescue T cell exhaustion and ICB resistance. Ex vivo treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…To better understand how the FLT3-ITD mutation in AML affects cDCs, we characterized cDCs in a mouse model of AML. Our lab has previously published work using AML mice that harbor the FLT3-ITD mutation and spontaneously develop AML to interrogate T cell dysfunction [36, 37]. Here we utilized mice that express one copy of FLT3-ITD under the endogenous FLT3 promoter, have a homozygous loss of TET2 and a homozygous loss of p53 using Cre-mediated deletion of LoxP-flanked alleles (AML mice) [21, 27, 38, 39].…”
Section: Resultsmentioning
confidence: 99%
“…To better understand how the FLT3-ITD mutation in AML affects cDCs, we characterized cDCs in a mouse model of AML. Our lab has previously published work using AML mice that harbor the FLT3-ITD mutation and spontaneously develop AML to interrogate T cell dysfunction [36, 37]. Here we utilized mice that express one copy of FLT3-ITD under the endogenous FLT3 promoter, have a homozygous loss of TET2 and a homozygous loss of p53 using Cre-mediated deletion of LoxP-flanked alleles (AML mice) [21, 27, 38, 39].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, abrogation of tumor sialylation facilitated CD8 + mediated tumor control and the recruitment of Tcf7 + CD8 + memory T cells within the TME. In multiple studies, Tcf7 + CD8 + memory T cells have been linked to ICI responses (15,16,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…to immune checkpoint inhibitor responses (15,16,(29)(30)(31)(32). The interference with sialylation therefore resulted not only in prolonged control of the breast tumors but, most importantly, also in breaking the resistance of breast tumors to anti-PD1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this in itself is of great interest, another study in AML found that BETi could effectively rescue both T cell exhaustion and immune cell blockade resistance. [ 5 ] The mechanism posited suggests that BETi act mechanistically to relieve the repression of progenitor programs in exhausted CD8+ T cells and restore and maintain a pool of anti‐PD1 responsive CD8+ T cells. [ 5 ] Indeed an earlier study in chronic lymphocytic leukaemia (CML), also found that BETi could reinvigorate exhausted T cells, [ 6 ] and moreover had potential applicability with respect to CD19‐targeted chimeric antigen receptor (CAR)‐T therapy.…”
mentioning
confidence: 99%
“…[ 5 ] The mechanism posited suggests that BETi act mechanistically to relieve the repression of progenitor programs in exhausted CD8+ T cells and restore and maintain a pool of anti‐PD1 responsive CD8+ T cells. [ 5 ] Indeed an earlier study in chronic lymphocytic leukaemia (CML), also found that BETi could reinvigorate exhausted T cells, [ 6 ] and moreover had potential applicability with respect to CD19‐targeted chimeric antigen receptor (CAR)‐T therapy. In this study, the authors found that for a subset of patients who relapsed upon CAR‐T‐based therapy, BET proteins were associated with the loss of the CAR, and this loss could be subsequently relieved by the use of BETi.…”
mentioning
confidence: 99%